Partisipasi Masyarakat dalam Pembentukan Undang-Undang Daerah Otonomi Baru Papua Perspektif Siyasah Dusturiyah - Muhammad Yahya (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The goal of this research is to know whether community participation participates in the establishment of the Papua Autonomy Regional Lawship and the establishment of the new Papuan autonomy law in accordance with the legislation process and the principles of formation of law in Islam, in which this research uses the library research (library research) with the normative juridical approach. The results of this study are that the establishment of the new autonomy of Papua has not yet met the participation of Papuans to engage in the formulation and preparation of the Papua DOBE LOVE, and that the formation of the Papua's DOBE Law in the sight of Siyasah Dusturiyah does not meet the principles of deliberations, freedom of expressing opinion and Jalb al-Masalih wa dar al-mafasid (take goodness and reject the ugliness).